FORMULASI GARAM DAN MADU TERHADAP KARAKTERISTIK MASKER WAJAH - Rika Diananing Putri; Imam Hanafi (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2022)
Salt is a natural product made from evaporation of sea water with the help of sunlight. The benefits of salt are many, both for food, health, and beauty needs. In addition, salt can treat skin diseases, overcome rough skin. Honey has good benefits for the health of the body, both externally and internally. The purpose of this study was to compile the ingredient formula and determine the effect of the raw material formula on the physical and organoleptic properties of facial mask products made from salt and honey. The use of salt into beauty products (masks for the face) by formulating salt and honey (as skin moisturizers) on physical and chemical characteristics. The stages of the research method used a completely randomized design (CRD) with 2x3 factorial sequentially between honey and salt GM1 (6%:20%), GM2 (6%:30%), GM3 (6%:50%), GM4 (8% :20%), GM5 (8%:30%), GM6 (8%:50%), then chemically analyzed including initial analysis and product analysis (pH). The progress of research results, chemically, in the treatment of GM1-GM3 has a pH of 6, while GM4-GM6 has a pH of 5. In accordance with the skin pH between 4-8. Physically, the color produced is cream, the aroma is odorless, and the homogeneity is the same. External status must be achieved.